EFFECT OF COMMON CARP (Cyprinus carpio) PITUITARY GLAND INJECTED WITH DIFFERENT DOSE ON OVULATION ANDSURVIVALN RATE OF KOMET (Carassius auratus) - Pratama, Rama Arif; Nuraini, Nuraini; Aryani, Netti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted from January to February 2018 in the halls 0f the fishery seeds Tarantang Subsdistrict, Harau, West Sumatra Province. The aims of this research was to know the effect of common carp (Cyprinus carpio) pituitary gland injected with different dose on ovulation and survivaln rate of komet (Carassius auratus) and To find the best dose ot the pituitary gland to stimulate ovulation and survivaln rate of komet (Carassius auratus). This research used on experimental, one factor four treathment and three replications. The treatments were : HP0: control with NaCl 0,9% (0,2 ml), HP3: Injected with 1:3 dose (1 kg of recipient : 3 kg of donor), HP4: Injected with 1:4 dose (1 kg of recipient : 4 kg of donor), and HP5: Injected with 1:5 dose (1 kg of recipient : 5 kg of donor). The results showed that common carp (Cyprinus carpio) injected gave an effect on ovulation and survival rate of komet (Carassius auratus). The treatment in HP1 : Injected with 1:3 dose (1 kg of recipient : 3 kg of donor) were teh best treatment with an average of latent time 6 haurs 3 minites , fertilization rate (FR) 69,74%, hatching rate (HR) 75,41% and 7 day survival rate of komet larvae with 90,87%.Keyword : Pituitary gland, ovulation, survival rate, Carassius auratus